DERIVATIVES: HEDGING AND SPECULATION (Globalization and Business, 2023)
The purpose of the article is to demonstrate: risks arising on the securities market, the goals of hedgers and speculators. The paper discusses the main features of derivatives (the most popular securities on the modern financial markets, such as futures, options, forwards).